The effect of vitamin D on insulin resistance in patients with type 2 diabetes - Talaei, Afsaneh (BioMed Central, 2013)
INTRODUCTION: Over the past decade, numerous non-skeletal diseases have been reported to be associated with vitamin D deficiency including type2 diabetes mellitus (T2DM). Different studies provide evidence that vitamin D may play a functional role in glucose tolerance through its effects on insulin secretion and insulin sensitivity. This study evaluates the effects of vitamin D supplementation on insulin resistance in T2DM. METHOD: Through a before-after study, 100 patients with T2DM, 30–70 years old, were recruited from an Arak diabetes clinic as consecutive attenders. Participants were assessed for clinical and biochemistry. Serum insulin and, 25(OH)D concentration, and HOMA-IR was calculated. All measurements were performed at the beginning and the end of the study. Patients received 50,000 unit of vitamin D(3) orally per week for eight weeks, Statistical analysis was made using SPSS17. The results were analyzed by descriptive tests, and a comparison between variables were made using paired T-tests or Wilcoxon tests, as appropriate. RESULTS: 100 participants including 70 women (70%) and 30 men (30%) took part in the study. All results were presented as Mean±SD, or medians of non-normally distributed. 24% of the participants were Vitamin D deficient {serum 25(OH)D ≤ 20 ng/ml(50 nmol/l)}. Mean serum 25 (OH) D concentration was 43.03± 19.28 ng/ml (107.5±48.2 nmol/l). The results at baseline and at the end, for FPG were 138.48±36.74 and 131.02±39 mg/dl (P=0.05), for insulin, 10.76±9.46 and 8.6±8.25 μIu/ml (P=0.028) and for HOMA-IR, 3.57±3.18 and 2.89±3.28 (P=0.008) respectively. CONCLUSION: Our data showed significant improvements in serum FPG, insulin and in HOMA-IR after treatment with vitamin D, suggested that vitamin D supplementation could reduce insulin resistance in T2DM.